2022
DOI: 10.3390/jof8020162
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Stropharia rugosoannulata Reveals Its Nutritional Strategy and Application Potential in Bioremediation

Abstract: Stropharia rugosoannulata is not only a popular edible mushroom, but also has excellent potential in bioremediation. In this study, we present a high-quality genome of a monokaryotic strain of the S. rugosoannulata commercial cultivar in China. The assembly yielded an N50 length of 2.96 Mb and a total size of approximately 48.33 Mb, encoding 11,750 proteins. The number of heme peroxidase-encoding genes in the genome of S. rugosoannulata was twice the average of all of the tested Agaricales. The genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We discovered a significant increase in soil nutrient content in paddy fields, which may be a result of significant changes in microbial communities within the paddy fields’ anaerobic environment ( Breidenbach et al, 2016 ). In addition, the genome sequencing of S. rugosoannulata revealed that it possesses powerful bioremediation and lignin degradation capabilities, so the secondary metabolites that can be produced can significantly improve soil nutrient levels ( Yang et al, 2022 ). It has been demonstrated that the used mushroom stock remaining after the fruiting bodies have been harvested adds many nutrients to the soil ( Gong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We discovered a significant increase in soil nutrient content in paddy fields, which may be a result of significant changes in microbial communities within the paddy fields’ anaerobic environment ( Breidenbach et al, 2016 ). In addition, the genome sequencing of S. rugosoannulata revealed that it possesses powerful bioremediation and lignin degradation capabilities, so the secondary metabolites that can be produced can significantly improve soil nutrient levels ( Yang et al, 2022 ). It has been demonstrated that the used mushroom stock remaining after the fruiting bodies have been harvested adds many nutrients to the soil ( Gong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. rugosoannulata mushrooms are being cultivated widely in various regions of China, which contributes to an efficient and sustainable circular economy, integrating agriculture and animal husbandry, achieving economic and ecological benefits, and combining land use with soil improvement. The mycelia are able to degrade cellulose and lignin through the secretion of extracellular enzymes, effectively utilizing agricultural and forestry residues such as straw and fallen leaves [15]. It can also reduce the concentration of Escherichia coli in water [16], mitigate nematode damage to vegetable roots [17], remediate soil contaminated with wood preservatives, and degrade toxic substances [18].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme activities, particularly laccase activity, can reflect mycelial vitality to some extent and correlate with mycelial growth and fruiting body development [37][38][39]. Genomic functional annotation and analysis of cell wall-degrading enzymes indicated a rich lignocellulase system of S. rugosoannulata [15,40]. Various agricultural and forestry residues can be used as substrates for cultivating, which contain abundant lignocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…S . rugosoannulata is consumed in large quantities and cultivated in many countries due to its superior taste and pharmacological activity ( Yang et al, 2022 ). Other studies have shown that S .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is recommended by the Food and Agriculture Organization as a good food source for developing countries (Li et al, 2022). S. rugosoannulata is consumed in large quantities and cultivated in many countries due to its superior taste and pharmacological activity (Yang et al, 2022). Other studies have shown that S. rugosoannulata could degrade environmental pollutants (bisphenol A, 2,4,6-trinitrotoluene, dibenzo-p-dioxins, and dibenzofurans) and plays an important role in soil remediation (Weiss et al, 2004;Kabiersch et al, 2011;Anasonye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%